Free-range broiler production as an alternative income for family farming in the northwest of Minas-MG - Mendes, Regiane Cristine Joslin; Moura, Guilherme de Souza; Mota, Diego Azevedo; Pereira, Anderson Alvarenga; Melo, Thiago Vasconcelos (Revista de Ciências Agroveterinárias, 2023)
Many family farmers use cooperativism as a tool to strengthen productive environments and envision productive diversification as an income generation strategy. This study analyzed the diversification project promoted by CAPUL in 2020, in the municipality of Arinos - MG, focusing on the production of free-range birds (Gallus gallus domesticus) to supply the demand for school meals and local commerce. The objective of this study was to analyze the economic and social impacts that the project generated in the lives of family farmers and elucidate the relevance of cooperativism for the promotion of productive diversification, as well as to highlight the detachments and obstacles that existed during the execution of the project. The self-administered questionnaire was used as the primary data source, considering a universe of 14 family farmers. The data were obtained through qualitative and quantitative instruments and were tabulated using the Microsoft Excel program. For descriptive statistical analysis of the results, a cluster analysis was used with the hierarchical method by the Ward model. It is concluded with this research that the project entitled Frango Caipirão CAPUL caused impacts on the lives of family farmers and that the cooperative, through its ATER actions, exerted influences on the social and economic reproduction of the participants of that study, contributing to the strengthening family farming. It is implied, therefore, that other actions in the same segment can use this master’s dissertation as a guideline.